PENGARUH MACAM BAHAN STEK DAN KONSENTRASI FILTRAT BAWANG MERAH (Allium cepa fa. ascalonicum, L.) TERHADAP PERTUMBUHAN BIBIT JAMBU AIR (Syzygium aqueum, Burm) VARITAS CITRA - Ismiterra Cahya Pradani; Hadi Rianto; Yulia Eko Susilowati (Universitas Tidar, 2019)
A research on the effect of cuttings material and concentration of shallot filtrate (Allium cepa fa. ascalonicum, L.) is to determine the growth of rose apple seedlings (Syzygium aqueum, Burm.) Citra variety. The Research was conducted from August until October 2018 in Mranti Pereng Village, Mranti Village, Purworejo District, Purworejo Regency. The altitude is 100 meters. Soil type latosol and soil pH 5.5. The research method used factorial experiment (3 x 4) arranged in a randomize complete block design with three blocks. The first factor is kinds of cuttings material, top cuttings, middle branch cuttings, and base branch cuttings. The second factor is concentration of shallot filtrate, 25%, 50%, 75%, and 100%. The results showed that the middle branch cuttings gives the highest yield in root length and root dry weight. The concentration of shallot filtrate gives regular results on observational parameters. The middle branch cuttings with concentration of shallot filtrate 76.49% gave the highest weigth yield on fresh shoots weight. The middle branch cuttings with concentration of shallot filtrate 87.30% giving the highest weigth yield on shoots dry weight. The middle branch cuttings with concentration of shallot filtrate 66.03% gives the highest weigth yield on roots dry weight